DINAMIKA PERLOMBAAN EKSPLORASI ANTARIKSA (SPACE RACE) ANTARA AMERIKA SERIKAT DAN TIONGKOK (2007 – 2016) - June cah (UNIDA Gontor, 2018)
Based on the consensus of international regime, the outer space is de-fined as one of the common goods of the mankind, which is non-appropri-ated and free utilized area. Historically, the utilization of the outer space has contributed to the human civilization. Innovation on science and tech-nology, however, has revolutionized outer space as a commercialized, in-dustrialized and militarized area, subject to the state’s national interest. The privilege and potential of outer space have become an anomaly, as profit-seeker parties such as state and private company attempt to take over the outer space, which create the space race. Since the first successful landing on the moon in 1960, the United States appears as the only giant space power, yet, recently, China also appears as one of the leading countries in outer space. The rise of China has put security dilemma in effect to the United States. From 2007 the conflict escalation between the United States and China on space exploration has increased due to several actions that threatening each country. The paper attempts to implement the concept of Game Theory, such as tit for tat strategy to minimize the possible loss and maximize the possible gain in decision-making process, in explaining the behavior of the United States and China and projecting their power-based interest on space.